Peran Dakwah Melalui Konten K-Pop Pada Generasi Z - Noviana Aini (CBJIS: Cross-Border Journal of Islamic Studies, 2024)
Generation z is a generation that is familiar with technology and popular culture, including k-pop. This is an opportunity for da'wah to reach this generation in preserving Islamic values in a creative and interesting way. One of them is using k-pop content. The role of da'wah has an important role in the spread of Islam Rahmatan lil'Alamin, especially for young people of generation Z. The spread of da'wah on social media by utilizing k-pop content is quite interesting to study. The formulation of the problem is: (1) what is the role of k-pop da'wah content in generation Z. (2) how does generation Z respond after seeing k-pop da'wah content posts. The type of research used in this study is descriptive qualitative research with a netnography approach. The analysis used in analyzing the problems in this study is thematic analysis and content analysis to find out virtual interactions with some followers of generation Z or even other account users (no followers) and how generation Z responds after seeing k-pop da'wah content posts. The results of this study show that da'wah through k-pop content is not only carried out conventionally but can be done through various media. This shows that da'wah through k-pop content is effective in attracting the attention of generation Z in a way that is easy to understand and remember. So that some followers or other account users can strengthen their beliefs, form a good character, and live a life in accordance with the guidance of Islam spread through k-pop content.